The Effect of Capital Risk on Optimal Saving Decisions - Hanson, David L.; Menezes, Carmen F. (Quarterly Journal of Economics, 1978)
I. Introduction, 653. — II. Preferences for sure and risky consumption bundles, 654. — III. Saving under certainty and under capital risk, 659. — IV. Comparison with the literature, 665.